TLX: An elusive receptor. Issue 157 (March 2016) - Benod, Cindy; Villagomez, Rosa; Webb, Paul
Highlights: TLX is a promising therapeutic target. Ligands need to be identified for TLX. TLX is druggable. Designing potent and specific TLX ligands is challenging. Abstract: TLX (tailless receptor) is a member of the nuclear receptor superfamily and belongs to a class of nuclear receptors for which no endogenous or synthetic ligands have yet been identified. TLX is a promising therapeutic target in neurological disorders and brain tumors. Thus, regulatory ligands for TLX need to be identified to complete the validation of TLX as a useful target and would serve as chemical probes to pursue the study of this receptor in disease models. It has recently been proved that TLX is druggable. However, to identify potent and specific TLX ligands with desirable biological activity, a deeper understanding of where ligands bind, how they alter TLX conformation and of the mechanism by which TLX mediates the transcription of its target genes is needed. While TLX is in the process of escaping from orphanhood, future ligand design needs to progress in parallel with improved understanding of (i) the binding cavity or surfaces to target with small molecules on the TLX ligand binding domain and (ii) the nature of the TLX coregulators in particular cell and disease contexts. Both of these topics are discussed in this review.